A rare gastric lesion: Russel body gastritis - Mehmet Suat Yalçın; Melike Ordu (Gastroenterology Review)
Russell body gastritis was first described by Tazawa and Tsutsumi, and it is a very rare medical condition. Russell body gastritis is a condition in which the lamina propria of the gastric mucosa are over-infiltrated by plasma cells containing Russell bodies, which are eosinophilic intracytoplasmic inclusions. Yu et al. reported a similar case in South Korea in 1987, which was not described as Russell body gastritis at the time. There are very few case reports in the literature. Some of them have been associated with Helicobacter pylori infection. However, it has been reported in HIV-positive cases that are not due to H. pylori.